Design of confocal waveguide interaction structure for a 220 GHz gyro-TWT. Issue 6 (13th April 2017) - Liu, Dagang; Tang, Xinbing; Yan, Yang; Wang, Huihui; Meng, Lin
Abstract: The high frequency characteristics of confocal waveguide interaction structure are studied, by which the confocal radius and mirror width of the confocal 220 GHz gyro-traveling-wave tube (gyro-TWT) are obtained. The characteristics of coupled dispersion curve, absolute instability, and backward wave oscillation are analyzed. Based on such analysis, methods that are using two lossy severs to suppress backward wave oscillation in 220 GHz gyro-TWT are put forward. Moreover, the experiment and numerical simulation of interaction structure of gyro-TWT with one lossy sever and the full three-dimensional numerical simulation of interaction structure of 220 GHz gyro-TWT with two lossy severs are carried out. The simulation results with two lossy severs show a peak output power of 10.7 kW, a peak efficiency of 11.65%, a peak gain of 25.5 dB, and a 1 dB bandwidth of 2.3 GHz.